Hematology and Physiology of Striped Catfish (Pangasianodon hypophthalmus) with the addition of guava leaf extract (Psidium guajava L) - Pohan, Ilham Fajri; Riauwaty, Morina; Syawal, Henni (Jurnal Perikanan dan Kelautan, 2024)
Striped catfish (Pangasianodon hypophthalmus) is a widely cultivated type of superior food fish. Intensive cultivation of catfish can cause disease. Feeding striped catfish with guava leaf extract is expected to reduce stress, which can be seen in striped catfish's hematological and physiological conditions. This research aims to obtain a dose of guava leaf extract (Psidium guajava L) to improve the health of striped catfish. The method used in the study was an experimental method that applied a one-factor, Completely Randomized Design (CRD) with five treatment levels. The treatment used was without adding guava leaf extract (P0); P1, P2, P3, and P4 with doses of 25, 50, 75, and 100 mL/kg feed, and all treatments were tested against Aeromonas hydrophila. The fish used in this research were 250 striped catfish seeds measuring 6-8 cm and kept for 45 days. Feeding with the addition of guava leaf extract at a dose of 75 mL/kg of feed had an influence on the hematological and physiological profile of post-challenge catfish, such as total erythrocytes of 2.40x106 cells/mm3, hematocrit 35.66%, hemoglobin levels 9.61 g/dL, total leukocytes 10.54x 104 cells/mm3, blood glucose levels of 78.00 mg/dL and phagocytic activity 35.66%. Absolute weight growth 17.76 g, feed efficiency 41.07%.